Penguatan Kapasitas Guru Dan Komunitas Belajar SMPN 16 Malang melalui Pendampingan Project Based Learning (PJBL) - Istikomayanti, Yuswa (Universitas Islam Balitar, 2025)
Mentorship for educators was conducted as part of a community engagement initiative and research dissemination effort, focusing on the topic of Project-Based Learning (PjBL). The subjects of this community service activity were 45 teachers from SMPN 16 Malang, who had participated in a workshop aimed at strengthening the Pancasila student profile and fostering